Brain Waves and Connectivity of Autism Spectrum Disorders - Norsiah, Fauzan; Nur Hurunain, Amran (Elsevier Ltd., 2015)
This research reports the brain waave pattern of individuals with ASD and to pinpoint the anomalies of ASD and its difference with the normal group. The findings revealed a general disruption in the overall connectivity of the different lobes known as hyper or hypo connectivity with excessive presence of slow wave (delta) at the frontal lobe and deficiency of beta in most of the brain regions. Other anomalies includes low alpha at the sensory motor regions, excess alpha in the left hemisphere and excess theta in the right frontal region. These anomalies explain the associated problem in attention, anxiety and social behaviors of ASD.